Self-cleaning paper-based coating and preparation method and application thereof

CN118773951BActive Publication Date: 2026-10-30QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410987240.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2026-10-30
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

[0005]针对现有技术中纸基涂料可生物降解性差、TiO2纳米粒子易团聚,掺杂进入的TiO2容易脱落的问题,本发明提供了一种自净化纸基涂料及其制备方法和应用,该纸基涂料涂敷于纸基材料表面,有望可以解决纸基封边条的空气净化作用

Benefits of technology

[0017]本发明通过将蓖麻油、盐酸多巴胺和纳米TiO2引入聚氨酯涂料中,制备自净化纸基涂料,并将该涂料涂覆于纸基材料表面,不仅可以赋予纸基材料净化空气的功能,而且在达到使用年限后,可以自行降解,不会对环境和人类健康产生危害。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118773951B_ABST
    Figure CN118773951B_ABST
Patent Text Reader

Abstract

The application discloses a kind of self-cleaning paper-based paint and its preparation method and application, self-cleaning paper-based paint includes end double hydroxyl polyol, double isocyanate, castor oil, dopamine hydrochloride, nano TiO2;The molar ratio of hydroxyl in double hydroxyl polyol and isocyanate radical in double isocyanate is 1:2;The molar ratio of hydroxyl in castor oil and isocyanate radical in double isocyanate is 1:4;The molar ratio of dopamine hydrochloride and isocyanate radical in double isocyanate is 1:2;The molar ratio of nano TiO2 and dopamine hydrochloride is 1:1~1:2.The application introduces castor oil, dopamine hydrochloride and nano TiO2 into polyurethane paint, prepares self-cleaning paper-based paint, and coats the paint on the surface of paper-based material, which not only can give paper-based material the function of purifying air, but also can degrade itself after reaching the service life, without harm to the environment and human health.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pulping and papermaking additives, specifically to a self-cleaning paper-based coating, its preparation method, and its application. Background Technology

[0002] With the rapid development of the forestry industry, the wood-based panel industry has also experienced rapid growth. From 2011 to 2020, my country's wood-based panel production and consumption grew simultaneously, with the national average annual growth rate of wood-based panel production approaching 7.3% and the average annual growth rate of consumption approaching 8.4%, both exceeding the production growth rate. In 2020, my country's total wood-based panel production reached 311.01 million cubic meters. 3 It grew by 0.8% year-on-year, with an output value of 706.577 billion yuan. Its consumption ranked first in the world, at approximately 296.16 million cubic meters. 3 This represents a year-on-year increase of 0.8%. According to relevant research, approximately 10% of in-use engineered wood products and related products will be discarded after several years, resulting in about 30 million m³ of waste engineered wood products in my country. It is worth noting that the edge banding strips for decorative particleboard, decorative fiberboard, and other decorative engineered wood products are mainly made of plastics such as PVC, ABS, PP, and PMMA. Their main functions are aesthetics, controlling the release of volatile organic compounds (such as formaldehyde) from the board, waterproofing, moisture resistance, and extending the lifespan of the board. However, because the components of these plastics are difficult to degrade, the cost of post-disposal is high, and they easily pollute the environment. Therefore, driven by both the "plastic restriction order" and the "paper-for-plastic" policy, developing high-performance paper-based materials to replace traditional plastic edge banding strips is expected to solve the problems existing in my country regarding the disposal of waste engineered wood products.

[0003] Paper is a natural polymer material made from plant fibers through a series of pulping and papermaking processes. Its molecular structure contains a large number of hydroxyl groups and porous structures, resulting in high swelling behavior and inherent sensitivity to liquid water and moisture. Therefore, functional agents are typically blended with a polymer matrix to prepare coating liquids, which are then applied to the paper surface to enhance the multifunctionality of the paper-based material. Based on this, to meet the application requirements of coatings in paper-based edge banding strips, the paper-based coatings must possess the following functions: First, the coating must be biodegradable. Paper-based coatings are typically based on petroleum-based compounds (such as fluorinated compounds, polyethylene, and waxes) to modify the wettability, water resistance, and barrier properties of paper. However, these coatings are poorly recyclable and lack biodegradability, posing a threat to the environment and human health, and even releasing greenhouse gases. Therefore, addressing the biodegradability of paper-based coatings is crucial.

[0004] Furthermore, the ability of furniture sealing strips to resist organic pollutants (such as formaldehyde) is crucial. TiO2's photocatalytic oxidation can degrade formaldehyde into carbon dioxide and water without forming other harmful byproducts. Therefore, TiO2 can be incorporated into paper-based coatings to catalyze the degradation of formaldehyde. However, TiO2 nanoparticles suffer from problems such as easy agglomeration, difficulty in recycling TiO2 powder, and the potential for secondary pollution. Therefore, while TiO2 is often embedded into paper-based coatings through doping, it is prone to detachment during later use. Summary of the Invention

[0005] In view of the problems of poor biodegradability of paper-based coatings, easy aggregation of TiO2 nanoparticles, and easy shedding of doped TiO2 in existing technologies, this invention provides a self-purifying paper-based coating, its preparation method and application. This paper-based coating is applied to the surface of paper-based materials and is expected to solve the air purification function of paper-based edge banding strips.

[0006] This invention is achieved through the following techniques and solutions: A self-cleaning paper-based coating comprises a dihydroxyl-terminated polyol, a diisocyanate, castor oil, dopamine hydrochloride, and nano-TiO2. The molar ratio of hydroxyl groups in dihydroxyl polyols to isocyanates in diisocyanates is 1:2; the molar ratio of hydroxyl groups in castor oil to isocyanates in diisocyanates is 1:4; the molar ratio of dopamine hydrochloride to isocyanates in diisocyanates is 1:2; and the molar ratio of nano-TiO2 to dopamine hydrochloride is 1:1 to 1:2.

[0007] Furthermore, the terminal dihydroxyl polypolyol is one or more of polyethylene glycol, polytetrahydrofuran, and polycaprolactone; the diisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, and L-lysine diisocyanate.

[0008] Furthermore, the molecular weight of the terminal dihydroxyl polyol is 800~5000 g / mol; the size of the nano-TiO2 is 15~150 nm.

[0009] The method for preparing the self-cleaning paper-based coating of the present invention is characterized by comprising the following steps: (1) A condensation reaction of a dihydroxyl-terminated polyol and a diisocyanate under the action of a catalyst is carried out to synthesize a polyurethane prepolymer with a diisocyanate-terminated group; (2) Castor oil was added to the reaction system in step (1) and reacted with isocyanate to prepare hyperbranched polyurethane. (3) Dopamine hydrochloride is added to the reaction system in step (2). The amino group in dopamine hydrochloride reacts with the isocyanate group, so that dopamine hydrochloride is grafted to the end of the polyurethane. (4) Add nano TiO2 to the reaction system in step (3), adjust the pH to 8~10 to carry out the reaction, and obtain the self-purified paper base coating.

[0010] Furthermore, in step (1), the temperature of the condensation reaction is 40~80℃ and the reaction time is 3~8h; in step (2), the temperature of the condensation reaction is 30~80℃ and the reaction time is 3~6h; in step (3), the temperature of the reaction is -10~20℃ and the reaction time is 1~5h.

[0011] Furthermore, the reaction temperature in step (4) is -10 to 20°C, and the reaction time is 1 to 5 hours.

[0012] Furthermore, the terminal dihydroxyl polyol, diisocyanate, castor oil, and dopamine hydrochloride are dissolved in DMF solvent.

[0013] Furthermore, the catalyst in step (1) is dibutyltin dilaurate; and the pH is adjusted using triethylamine in step (4).

[0014] Application of a self-cleaning paper-based coating in the preparation of self-cleaning paper-based materials.

[0015] Furthermore, the self-cleaning paper-based coating is applied to the surface of the paper-based material.

[0016] Among numerous biomass raw materials, castor oil, with its abundant hydroxyl groups and double bonds in its molecular structure, is relatively easy to chemically react with. Therefore, using it as a raw material to synthesize paper-based coatings can effectively improve the biodegradability of these coatings. Dopamine hydrochloride can adhere to the surface of organic or inorganic matrix materials, and it possesses abundant semiquinone and quinone functional ligands, enabling coordination with various metal ions. Therefore, by coordinating dopamine hydrochloride with TiO2, TiO2 can be embedded into the paper-based coating, which, when applied to the paper material surface, is expected to solve the air purification function of paper-based edge banding strips. This invention, through the rational design of polymer molecular structures, introduces castor oil and TiO2 into polymers to prepare a paper-based coating. After coating the paper material surface, the biodegradability of castor oil and the photocatalytic function of TiO2 enhance the biodegradability and formaldehyde catalytic ability of the paper material. Specifically, a polyurethane coating is constructed with a polyurethane prepolymer composed of polyol and isocyanate as the branch chain, castor oil as the core, dopamine hydrochloride as the terminal group, and TiO2 as the crosslinking agent. The high adhesion, water resistance and self-cleaning function of the paper-based coating are achieved through the following mechanism: (1) When the coating is applied to the paper surface, the solution in the coating penetrates into the cellulose, causing the cellulose to swell slightly, reducing the strong hydrogen bonding force in the cellulose, causing some of the -OH in the cellulose to become free. At this time, the -NCO in the coating rapidly reacts with the free -O in the cellulose under the action of the catalyst in the solution. H reaction, penetrate into the interior of cellulose, bind tightly with the fiber, and firmly adhere to the surface of paper-based cellulose, making it difficult to fall off; (2) A large amount of -OH in the coating can improve the adhesion between the coating and paper-based cellulose; (3) The cross-linking effect between castor oil and polyurethane prepolymer in the coating can effectively prevent water molecules from diffusing into the paper-based sealing strip, thereby playing a waterproof role; (4) TiO2 in the coating is firmly locked in the polymer by forming a coordination compound with dopamine hydrochloride. When the sunlight is sufficient, TiO2 in the coating can catalyze the degradation of formaldehyde gas in the room. Beneficial effects

[0017] This invention prepares a self-purifying paper-based coating by introducing castor oil, dopamine hydrochloride, and nano-TiO2 into a polyurethane coating. The coating is then applied to the surface of the paper-based material, which not only gives the paper-based material the function of purifying the air, but also degrades itself after reaching its service life, without causing harm to the environment or human health. Attached Figure Description

[0018] Figure 1 The graphs show the mechanical properties of the self-cleaning paper-based coatings prepared in Examples 1-4 after film formation. Figure 2The graph shows the degradation of paper-based materials. a) Paper-based material in Example 1 degrades in 0 days; b) Paper-based material in Example 1 degrades in 90 days; c) Paper-based material in Comparative Example 5 degrades in 0 days; d) Paper-based material in Comparative Example 5 degrades in 90 days. Figure 3 Figure showing the mass loss of paper-based materials at different degradation times. Detailed Implementation

[0019] The preparation method and application of a self-cleaning paper-based material of the present invention will be further described below with reference to specific embodiments. These specific embodiments are for further detailed explanation of the present invention and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the reagents, equipment, and methods used in the present invention are commercially available reagents, equipment, and methods conventionally used in this technical field. Example

[0020] (1) 4.0 g of polyethylene glycol (Mn=800 g / mol) was dried under vacuum at 120℃ for 2 h and then placed in a three-necked flask containing 10 mL of N,N-dimethylformamide (DMF). It was then dissolved evenly under mechanical stirring at 200 r / min and 40℃. 2.22 g of isoflurane diisocyanate was dissolved evenly in 10 mL of DMF and then slowly added to the polyethylene glycol solution using a constant pressure dropping funnel under nitrogen protection. 0.005 g of dibutyltin dilaurate was added to the reaction system. After condensation reaction for 8 h, polyurethane prepolymer with terminal isocyanate group was obtained. (2) Dissolve 0.78g castor oil in 20mL DMF and slowly add it to the reaction system of step (1). React for 4h under mechanical stirring at 80℃ and 200r / min to condense with isocyanate and prepare hyperbranched polyurethane with castor oil as the core. (3) Adjust the temperature of the reaction system in step (2) to -10℃. Dissolve 0.47g of dopamine hydrochloride in 10mL of DMF and slowly add it to the reaction system. After reacting for 2 hours, the amino groups in dopamine hydrochloride react with the isocyanate group, so that dopamine hydrochloride is grafted to the end of the polyurethane. (4) Dissolve 0.20g of TiO2 with a diameter of 10nm in 10mL of DMF and add it to the reaction system of step (3). Adjust the pH of the system to 8 with triethylamine. After reacting for 5h at -10℃, the reaction is stopped. After removing most of the solvent by rotary evaporator, the self-purified paper base coating is obtained. Example

[0021] (1) 24.9 g of polytetrahydrofuran (Mn=5000 g / mol) was dried under vacuum at 120℃ for 2 h and then placed in a three-necked flask containing 10 mL of N,N-dimethylformamide (DMF). It was then dissolved evenly under mechanical stirring at 200 r / min and 80℃. 1.68 g of hexamethylene diisocyanate was dissolved evenly in 10 mL of DMF and then slowly added to the polytetrahydrofuran solution using a constant pressure dropping funnel under nitrogen protection. 0.005 g of dibutyltin dilaurate was added to the reaction system. After condensation reaction for 3 h, polyurethane prepolymer with terminal isocyanate group was obtained. (2) Dissolve 0.78g castor oil in 20mL DMF and slowly add it to the reaction system of step (1). React for 4h under mechanical stirring at 30℃ and 200r / min to react with isocyanate and prepare hyperbranched polyurethane with castor oil as the core. (3) Adjust the temperature of the reaction system in step (2) to 20℃. Dissolve 0.47g of dopamine hydrochloride in 10mL of DMF and slowly add it to the reaction system. After reacting for 2 hours, the amino groups in dopamine hydrochloride react with the isocyanate group, so that dopamine hydrochloride is grafted to the end of the polyurethane. (4) Dissolve 0.10g of TiO2 with a diameter of 150nm in 10mL of DMF and add it to the reaction system of step (3). Adjust the pH of the system to 8 with triethylamine. After reacting for 1h at -10℃, the reaction is terminated. After removing most of the solvent by rotary evaporator, the self-purified paper base coating is obtained. Example

[0022] (1) 15g of polytetrahydrofuran (Mn=3000 g / mol) was dried under vacuum at 120℃ for 2h and then placed in a three-necked flask containing 10mL of N,N-dimethylformamide (DMF). It was then dissolved evenly under mechanical stirring at 200 r / min and 60℃. 2.26g of L-lysine diisocyanate was dissolved evenly in 10mL of DMF and then slowly added to the polytetrahydrofuran solution using a constant pressure dropping funnel under nitrogen protection. 0.005g of dibutyltin dilaurate was added to the reaction system. After condensation reaction for 6h, polyurethane prepolymer with terminal isocyanate group was obtained. (2) Dissolve 0.78g castor oil in 20mL DMF and slowly add it to the reaction system of step (1). React for 5h under mechanical stirring at 60℃ and 200r / min to condense with isocyanate to prepare hyperbranched polyurethane with castor oil as the core. (3) Adjust the temperature of the reaction system in step (2) to 20℃. Dissolve 0.47g of dopamine hydrochloride in 10mL of DMF and slowly add it to the reaction system. After reacting for 2 hours, the amino groups in dopamine hydrochloride react with the isocyanate group, so that dopamine hydrochloride is grafted to the end of the polyurethane. (4) Dissolve 0.10g of TiO2 with a diameter of 50nm in 10mL of DMF and add it to the reaction system of step (3). Adjust the pH of the system to 9 with triethylamine. After reacting for 1h at 20℃, the reaction is terminated. After removing most of the solvent by rotary evaporator, the self-purified paper base coating is obtained. Example

[0023] (1) 10g of polycaprolactone (Mn=2000 g / mol) was dried under vacuum at 120℃ for 2h and then placed in a three-necked flask containing 10mL of N,N-dimethylformamide (DMF). It was then dissolved evenly under mechanical stirring at 200 r / min and 60℃. 2.62g of dicyclohexylmethane diisocyanate was dissolved evenly in 10mL of DMF and then slowly added to the polyethylene glycol solution using a constant pressure dropping funnel under nitrogen protection. 0.005g of dibutyltin dilaurate was added to the reaction system. After condensation reaction for 7h, polyurethane prepolymer with terminal isocyanate group was obtained. (2) Dissolve 0.78g castor oil in 20mL DMF and slowly add it to the reaction system of step (1). React for 5h under mechanical stirring at 50℃ and 200r / min to condense with isocyanate and prepare hyperbranched polyurethane with castor oil as the core. (3) Adjust the temperature of the reaction system in step (2) to 10℃. Dissolve 0.47g of dopamine hydrochloride in 10mL of DMF and slowly add it to the reaction system. After reacting for 1h, the amino groups in dopamine hydrochloride react with isocyanate groups, so that dopamine hydrochloride is grafted to the end of the polyurethane. (4) Dissolve 0.20g of TiO2 with a diameter of 100nm in 10mL of DMF and add it to the reaction system of step (3). Adjust the pH of the system to 10 with triethylamine. After reacting at 10℃ for 2h, the reaction is stopped. After removing most of the solvent by rotary evaporator, the self-purified paper base coating is obtained.

[0024] Comparative Example 1 Compared with Example 1, in Comparative Example 1, TiO2 was not added. After dopamine hydrochloride was grafted onto the polyurethane end, most of the solvent was removed by rotary evaporation to obtain a paper-based coating.

[0025] Comparative Example 2 Compared with Example 2, in Comparative Example 2, TiO2 was not added. After dopamine hydrochloride was grafted onto the polyurethane end, most of the solvent was removed by rotary evaporation to obtain a paper-based coating.

[0026] Comparative Example 3 Compared with Example 3, in Comparative Example 3, TiO2 was not added. After dopamine hydrochloride was grafted onto the polyurethane end, most of the solvent was removed by rotary evaporation to obtain a paper-based coating.

[0027] Comparative Example 4 Compared with Example 4, in Comparative Example 4, TiO2 was not added. After dopamine hydrochloride was grafted onto the polyurethane end, most of the solvent was removed by rotary evaporation to obtain a paper-based coating.

[0028] Comparative Example 5 Compared with Example 1, Comparative Example 5 used non-biomass material terminal hydroxyl hyperbranched polyester instead of castor oil, and the remaining steps and reaction conditions were the same as in Example 1. (1) 4.0 g of polyethylene glycol (Mn=800 g / mol) was dried under vacuum at 120℃ for 2 h and then placed in a three-necked flask containing 10 mL of N,N-dimethylformamide (DMF). It was then dissolved evenly under mechanical stirring at 200 r / min and 40℃. 2.22 g of isoflurane diisocyanate was dissolved evenly in 10 mL of DMF and then slowly added to the polyethylene glycol solution using a constant pressure dropping funnel under nitrogen protection. 0.005 g of dibutyltin dilaurate was added to the reaction system. After condensation reaction for 8 h, polyurethane prepolymer with terminal isocyanate group was obtained. (2) Dissolve 0.42g of hyperbranched polyester with a molecular weight of 2000 and 12 hydroxyl groups at the end in 20mL of DMF, and slowly add it to the reaction system of step (1). React for 4h under mechanical stirring at 80℃ and 200 r / min to condense with isocyanate to prepare hyperbranched polyurethane. (3) Adjust the temperature of the reaction system in step (2) to -10℃. Dissolve 0.47g of dopamine hydrochloride in 10mL of DMF and slowly add it to the reaction system. After reacting for 2 hours, the amino groups in dopamine hydrochloride react with the isocyanate group, so that dopamine hydrochloride is grafted to the end of the polyurethane. (4) Dissolve 0.20g of TiO2 with a diameter of 10nm in 10mL of DMF and add it to the reaction system of step (3). Adjust the pH of the system to 8 with triethylamine. After reacting for 5h at -10℃, the reaction is stopped. After removing most of the solvent by rotary evaporator, the self-purified paper base coating is obtained.

[0029] Performance testing (1) The self-cleaning paper-based coatings prepared in Examples 1-4 were placed in polytetrafluoroethylene molds and then placed in an oven at 60°C to evaporate the solvent in the coatings, resulting in coating films. The mechanical strength of the films was measured using a universal tensile tester, and the results were recorded. Figure 1 As shown, by Figure 1It can be seen that the self-cleaning paper-based coatings prepared by the technical solution of the present invention all have high mechanical strength and can be used as paper-based coatings.

[0030] (2) The paper-based coating materials prepared in Example 1 and Comparative Example 5 were applied to the surface of paper to prepare paper-based materials. The paper-based materials were buried in soil and removed after 90 days to observe the degradation of the paper-based materials. The results are as follows: Figure 2 As shown, a is an image of the paper-based material of Example 1 after 0 days of degradation, b is an image of the paper-based material of Example 1 after 90 days of degradation, c is an image of the paper-based material of Comparative Example 5 after 0 days of degradation, and d is an image of the paper-based material of Comparative Example 5 after 90 days of degradation; Figure 2 It can be seen that the polyurethane paper-based coating synthesized with castor oil, when applied to the surface of the paper-based material and buried in the soil, has a better degradation effect. In contrast, the polyurethane paper-based coating synthesized with hyperbranched polyester, when applied to the surface of the paper-based material and buried in the soil, has a poorer degradation effect. (3) The weight loss of the paper-based materials prepared in different examples over time was determined by the mass loss method. The paper-based materials prepared in Examples 1-4 and Comparative Example 5 were buried in the soil, and the mass of the paper-based materials was measured at regular intervals. The mass loss rate was calculated according to the following formula.

[0031] ω=(m0-m) / m0×100%.

[0032] In the formula, ω is the weight loss rate of the pressed straw paper mulch film, %; m0 is the initial weight of the pressed straw paper mulch film, in grams; m is the weight of the straw paper mulch film after it has degraded over a certain period of time, in grams.

[0033] The mass loss of paper-based materials at different degradation times is shown in the figure below. Figure 3 As shown, by Figure 3 It can be seen that when the paper-based coatings prepared by the technical solutions described in Examples 1-4 of the present invention are applied to paper-based materials, the weight of the paper-based materials gradually decreases over time after being buried in the soil, which indicates that the paper-based materials have high degradability. However, when the paper-based coatings prepared by the scheme described in Comparative 5 are applied to paper-based materials, although they also have a certain degree of degradability, their degradation rate is significantly lower than that of Examples 1-4. This indicates that introducing castor oil into polyurethane paper-based coatings helps the coatings degrade.

[0034] (4) The paper-based coatings prepared by the technical solutions described in Examples 1-4 and Comparative Examples 1-4 were applied to paper-based materials to test their formaldehyde removal performance. The experimental scheme is as follows: Eight 20 mL portions of 100 mg / L formaldehyde were placed in 50 mL centrifuge tubes. The paper-based materials prepared in Examples 1-4 and Comparative Examples 1-4 were then tied with thread and suspended in the centrifuge tubes. The caps of the centrifuge tubes were tightened to ensure that the paper-based materials remained suspended (without contact with the formaldehyde solution below). The tubes were then exposed to sunlight for 2 hours. After the reaction was completed, the reaction apparatus was placed in cold water and allowed to stand for 30 minutes. The formaldehyde concentration in the centrifuge tubes was then measured according to the requirements of HJ601-2011, and the formaldehyde removal effect of the paper-based materials was calculated. The results are shown in Table 1 below.

[0035] The formula for calculating the formaldehyde removal effect is as follows: Q m =(C0-C)×V×n / m0 Q m C represents the amount of formaldehyde removed by the sample (mg / g); C0 represents the initial concentration of formaldehyde (mg / L); C represents the concentration of formaldehyde after removal (mg / L); V represents the volume of formaldehyde (mL); n represents the dilution factor; and m represents the amount of adsorbent used (g).

[0036] Table 1. Formaldehyde removal effect of paper-based materials. As can be seen from the comparison data in Table 1, when TiO2 is embedded in the paper-based coating, the formaldehyde removal effect of the paper-based material is significantly higher than that of the paper-based material without TiO2.

[0037] (5) To assess the formaldehyde removal efficiency of the paper-based testing material, we will use 0.25m 2 70g / m 2 The paper-based material was placed in a 1m 3 The formaldehyde concentration is 1 mg / m³ 3 After being exposed to sunlight for 24 hours in a sealed chamber, the residual concentration of formaldehyde in the sealed chamber was measured. The experimental results are shown in Table 2: Table 2 The effect of paper-based materials on formaldehyde gas removal. The comparative data in Table 2 show that when TiO2 is embedded in the paper-based coating, the paper-based material has a significantly higher formaldehyde removal efficiency than the paper-based material without TiO2. Furthermore, when the paper-based material contains TiO2, the residual formaldehyde concentration is consistently <0.07 mg / m³. 3 It meets the GB50325-2020 standard for indoor formaldehyde concentration ≤0.07 mg / m³. 3 Requirements.

Claims

1. A method for preparing a self-cleaning paper-based coating, characterized in that, Includes the following steps: (1) A condensation reaction of a dihydroxyl-terminated polyol and a diisocyanate under the action of a catalyst is carried out to synthesize a polyurethane prepolymer with a diisocyanate-terminated group; (2) In step (1), castor oil is added to the reaction system and undergoes a condensation reaction with isocyanate to prepare hyperbranched polyurethane; the molar ratio of hydroxyl groups in castor oil to isocyanate groups in diisocyanate is 1:4; the temperature of the condensation reaction is 30-80℃ and the reaction time is 3-6h. (3) Dopamine hydrochloride is added to the reaction system in step (2). The amino group in dopamine hydrochloride reacts with the isocyanate group, so that dopamine hydrochloride is grafted to the end of the polyurethane. (4) After dissolving nano-TiO2 in DMF, add it to the reaction system of step (3), adjust the pH to 8~10 to carry out the reaction, and obtain the self-purified paper base coating; the reaction temperature is -10~20℃, the reaction time is 1~5h; the molar ratio of nano-TiO2 to dopamine hydrochloride is 1:1~1:

2.

2. The method for preparing the self-cleaning paper-based coating according to claim 1, characterized in that, The temperature of the condensation reaction in step (1) is 40~80℃ and the reaction time is 3~8h; the temperature of the reaction in step (3) is -10~20℃ and the reaction time is 1~5h.

3. The method for preparing the self-cleaning paper-based coating according to claim 1, characterized in that, The terminal dihydroxyl polyol, diisocyanate, castor oil, and dopamine hydrochloride are dissolved in DMF solvent.

4. The method for preparing the self-cleaning paper-based coating according to claim 1, characterized in that, The catalyst in step (1) is dibutyltin dilaurate; the pH is adjusted using triethylamine in step (4).

5. The self-cleaning paper-based coating prepared by the preparation method according to any one of claims 1-4, characterized in that, Including terminal dihydroxyl polyols, diisocyanates, castor oil, dopamine hydrochloride, and nano-TiO2; The molar ratio of hydroxyl groups in the dihydroxy polyol to isocyanates in the diisocyanate is 1:2; the molar ratio of dopamine hydrochloride to isocyanates in the diisocyanate is 1:

2.

6. The self-cleaning paper-based coating according to claim 5, characterized in that, The terminal dihydroxyl polypolyol is one or more of polyethylene glycol, polytetrahydrofuran, and polycaprolactone; the diisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, and L-lysine diisocyanate.

7. The self-cleaning paper-based coating according to claim 5, characterized in that, The molecular weight of the terminal dihydroxyl polyol is 800~5000 g / mol; the size of the nano-TiO2 is 15~150 nm.

8. The application of a self-cleaning paper-based coating prepared by the preparation method according to any one of claims 1 to 4 in the preparation of self-cleaning paper-based materials.

9. The application according to claim 8, characterized in that, The self-cleaning paper-based coating is applied to the surface of the paper-based material.

Citation Information

Patent Citations

  • Nano diatomite-titanium dioxide-containing antibacterial purifying coating wallpaper

    CN105350401A

  • Antibacterial type castor oil based cationic-aqueous polyurethane emulsion and preparation method thereof

    CN107141439A

  • Steel surface self-passivating anticorrosive paint, and preparation method and application thereof

    CN112080198A